CRITICAL THINKING AS AN INDICATOR OF DECREASING THE LEVEL OF ANXIETY IN THE CONDITIONS OF INFORMATION AND PSYCHOLOGICAL WAR - Moroz, L.; Yakovenko, S. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2019)
The article reveals the possibility and feasibility of applying an environmental approach to understanding the mental state of the population, which considers itself a victim as a result of the information and psychological war that is being waged against the Ukraine by the media of the Russian Federation. At the individual level, personal anxiety factors are the properties of the higher nervous system, which determine endurance and sensitivity to the influence of stressors, flexibility of thinking, which contributes to successful adaptation to changing and unfavorable living conditions. The mental state of a person is largely dependent on the quality of life, the assessment of threats to well-being and safety.
Keywords: mental state of the population, information-psychological war, personal anxiety, higher nervous system, stressors, adaptation